Resumes de recherche 2001 - Center for International Forestry Research (Center for International Forestry Research, 2002)
This book is a compilation of the abstracts of in-house and external publications produced in the year 2001 by CIFOR scientists and their collaborators. The abstracts are grouped into seven themes: general, biodiversity, forest governance and community forestry, forest management, non-timber forest products, plantations and rehabilitation of degraded forests, policy and extrasectoral issues that represent CIFOR's research activities. Indexes are provided by author and keyword.